Hypo-Articulation of the Four-Way Voicing Contrast in Nepali Infant-Directed Speech. Issue 3 (3rd July 2019) - Benders, Titia; Pokharel, Sujal; Demuth, Katherine
ABSTRACT: Hyper-articulation of vowel and consonant contrasts is often reported in infant-directed speech (IDS), but is not universal cross-linguistically, and may be a side-effect of speaking rate. This study investigated the voicing characteristics of the four-way oral stop voicing contrast in Nepali IDS. Both lead and lag time of word-onset/ɡ, ɡʱ, k, kʱ/were measured in the IDS and adult-directed speech (ADS) of 16 Nepali-speaking mothers. The lower prevalence of contrastive prevoicing and shorter lead times in IDS compared to ADS indicate hypo -articulated voicing contrasts. Shorter overall lag times in IDS suggest that stop consonants are less salient in IDS compared to ADS. These results cannot be explained as a side-effect of speaking rate, but rather suggest an increased salience for vowels compared to consonants within the IDS syllable. The implications for the acquisition of voicing contrasts are discussed.